The timing of transition to senior surgical resident: A national survey of Canadian program directors - Mitchell, Eric C; DeLyzer, Tanya; Van Koughnett, Julie Ann; Grant, Aaron (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Introduction: Transitions within medical education are challenging and mark significant changes in responsibility and independence. The transition from junior to senior surgical resident has been sparsely examined. The purpose of this study was to evaluate the timing of this transition in Canadian surgical programs and the factors used to guide this decision.Methods: We developed a cross-sectional, single-stage survey and distributed it to all Canadian surgical program directors. We analyzed survey responses using quantitative methods.Results: Forty-seven program directors responded, representing all ten surgical disciplines. The most frequent period of transition from junior to senior resident was July of PGY-3. Programs that employ a formal “transition” curriculum for juniors had a significantly earlier transition, while programs that use staff feedback to guide the transition decision had a significantly later transition. Directors identified year of training and experience, technical ability, and clinical competence as key features of a senior surgical resident.Conclusions: Surgical residency programs largely use a time-based model to determine when residents transition from junior to senior resident. Future qualitative studies should examine the factors used to make transition decisions and explore how programs define a senior surgical resident.